Compliance audit model for managing process safety in process industries - Majid, N.D.A. (Trans Tech Publications Ltd, 2014)
Compliance audit for process safety management (PSM) is a technique to verify that the implementation of the PSM program is in compliance with OSHA standards and to identify potential deficiencies in the PSM program used. However, unavailability of an easy audit techniques hinders the compliances to PSM standards in industries. An audit model is introduced based on OSHA PSM standard to provide a standardize format that utilizes the Piping and Instrumentation Diagram (P&ID) as a basis. A case study based on the training element of OSHA PSM is performed to verify the effectiveness and to ensure the PSM standard compliances. The model is based on Microsoft Access which enables the user to input data, manage and track information. The model is useful to the employee as the weaknesses in the PSM program can be identified and rectified to prevent any major accidents. Â© 2014 Trans Tech Publications, Switzerland.